PESAN DAKWAH DALAM PODCAST YOUTUBE KOPIPANAS.CHANNELS EDISI #2 CAFEKITA – ULAS BUKU-CINTANYA HATI SUHITA - Husnul Inayah, Hasna; Slamet, Moh. (Spektra Komunika : Jurnal Komunikasi & Dakwah, 2024)
In this advanced and modern era, the activities of Islamic preaching (dakwah) have adapted to the current developments, particularly through the sophistication of social media. This study examines the preaching messages found in the YouTube Podcast titled "Kopipanas.channels Edisi #2 Cafekita - Ulas Buku-Cintanya Hati Suhita 14 November 2021". A Qualitative Descriptive Approach using the Holsti Content Analysis method is employed to address this issue. Primary data is gathered from YouTube Social Media, without the necessity of statistical data, but rather through the analysis of sentences and excerpts of the conveyed messages. The study categorizes the preaching messages into three main categories: creed (akidah), Islamic law (syari'at), and morality (akhlak), which constitute the core teachings of Islam. Through this approach and method, the study aims to describe these messages.